The causes of euro instability - Philip Arestis; Iris Biefang-Frisancho Mariscal; Andrew Brown; Malcolm Sawyer (Levy Economics Institute of Bard College, 2001)
This paper examines the causes of the general decline in the value of the euro by assessing the various explanations proffered in existing literature, then offering a more satisfactory explanation. The argument prevalent in the literature
Keywords: 330; that the decline in value of the euro is due to U.S. strength rather than to any inherent difficulties with its imposition